Grensesprenging - Saur, Ellen; Ness, Ottar (Fagbokforlaget Vigmostad & Bjørke, 2026)
Using three theatre companies—Access All Areas Productions (UK), Back to Back Theatre Company (Australia), and Teater nonSTOP (Norway)—this book shows, through examples and images, a rich and exciting artistic field. Here we meet performers who move audiences with innovative, and for many surprising, artistic expressions, creating existential encounters with their public. The book aims to develop understanding and knowledge of how competence development can be carried out and how one can collaborate with actors who have intellectual disabilities, autism, or others who experience barriers to participation. The companies presented challenge power structures both on stage and in the industry, and the current situation is discussed in light of the historical development within the disability field. In an entertainment industry where both stage and streaming services demand greater diversity, both individual and system knowledge are required for actors with intellectual disabilities and autism to have good working conditions and thus realize their artistic potential. As Ingrid Lorentzen writes in the book’s foreword: “New generations of artists will be inspired by the work of the artists this is about—artists who are not to be written into a history of exclusion or opposition, but who, through central artistic contributions, put people first.”